Emily Wind snap and the land of the Midnight Sun. - Kessler,Liz. (London Orion Children's, 2012)
Emily is back in this fifth installment, which jumps right into the story-- there are horrible storms arising, and they are caused by Neptune's nightmares. Emily and her friend Aaron (who are both semi-Mer, which means that they can exist both above and below water) head up to Alaska to try to find out what is going on. It turns out that Neptune has a twin brother, Njord, with whom he fought. Njord has been frozen and immobile for years, but once he is unfrozen, things start to heat up. Njord is angry at Neptune, and wants to get back at him. When Neptune once again fools around with memories, letting the narwhal take those from many of the main characters, Njord sees this as an opportunity to strike. Will Njord be able to take over Neptune's kingdom?
Keywords: English story book